Адміністративні особливості територіальних змін у сільських ґмінах Львівського повіту у 20-30-х рр. ХХ ст. - Захарчин, Н.; Zakharchyn, N. (My University, 2018)
Досліджено механізми удосконалення адміністративного устрою (на прикладі Львівського повіту) як один з елементів реформування у Другій Речі Посполитій. У міжвоєнний (1918 – 1939 рр.) період ближчі села Львівщини були об’єднані у Львівський повіт. Із становленням основ територіально-адміністративного законодавства в Польщі, проходили і відповідні зміни в регіоні, які аналізуються у статті. The article highlights the mechanisms of administrative structure improving as an element of reforming processes in Second Rzeczpospolita (case study of Lviv Povit). In the interwar period (1918-1939) the villages of Lviv region, located nearest to each other, were united into the Lviv Povit (district). The formation and utilization of the territorial-administrative law foundations in Poland brought about corresponding changes in the region: division of the Lviv Povit into smaller administrative units, the accession of the nearby villages to the city, the amalgamation of rural communes into the so-called collective gmina, and others. The changes were launched gradually. At the first stage there were constitutional, legislative, territorial-administrative and status changes, which took place practically in all territories of the revived Rzeczpospolita in the interwar period; then – withdrawal of the nearest to Lviv territories from the Lviv district. The third stage was the unifying stage in the discourse of self-governing reform in Poland. In the course of this reform Lviv district as a whole underwent significant transformations that were not always positive. Thus, as a result of the accession of suburban gminas to Lviv, the production and, therefore, the financial potential of the Lviv Povit has decreased significantly, and the creation of collective Gminas had not significantly improved the situation in the region, since the newly formed rural communities often failed to lead an independent economic life.
Administrative Specifics of the Territorial Changes in Rural Areas (Gminas) of Lviv Region in the 20-30's of the 20th cent
Keywords: ґміна; Львівський повіт; адміністративні зміні; територіальні зміни; Польща; міжвоєнний період; gmina; Lviv district; administrative changes; territorial changes; Poland; interwar period